Rekayasa Perangkat Lunak Pemetaan Perguruan Tinggi Berbasis Web di Kota Tangerang Selatan - Listiyo Arief Nugroho; Viky Ardiansyah; Muhammad Syaiful Arief; Aries Saifudin (Program Studi Teknik Informatika Universitas Pamulang, 2020)
Prospective students have the desire to continue their education to universities with faculties and departments that match their interests and talents. Many prospective students do not know the information related to the location of the university or faculty and department available at a university. In general, prospective students find out this information through the university's website or just information from the public. In South Tangerang City, there are already many universities or colleges in the South Tangerang City area. With the disain of the University Mapping WebGIS software in South Tangerang City, it is hoped that the information on universities around South Tangerang City can be easily recieved by prospective students. This software was developed with the Waterfall model, which this development model can make it easier for software developers to observe on planning or analysis before starting the development process. The result of using the Waterfall method is the Mapping College application in South Tangerang City. This mapping application can later be used by prospective students to find information about the location of universities in South Tangerang City or information related to faculties and departments available at a university.